Electrical and synaptic integration of glioma into neural circuits - Venkatesh, Humsa; Morishita, Wade; Geraghty, Anna C.; Silverbush, Dana; Gillespie, Shawn M.; Arzt, Marlene; Tam, Lydia T.; Espenel, Cedric; Ponnuswami, Anitha; Ni, Lijun; Woo, Pamelyn J.; Taylor, Kathryn R.; et al. (Nature, 2019)
High-grade gliomas are lethal brain cancers whose progression is robustly regulated by neuronal activity. Activity-regulated release of growth factors promotes glioma growth, but this alone is insufficient to explain the effect that neuronal activity exerts on glioma progression. Here we show that neuron and glioma interactions include electrochemical communication through bona fide AMPA receptor-dependent neuron-glioma synapses. Neuronal activity also evokes non-synaptic activity-dependent potassium currents that are amplified by gap junction-mediated tumour interconnections, forming an electrically coupled network. Depolarization of glioma membranes assessed by in vivo optogenetics promotes proliferation, whereas pharmacologically or genetically blocking electrochemical signalling inhibits the growth of glioma xenografts and extends mouse survival. Emphasizing the positive feedback mechanisms by which gliomas increase neuronal excitability and thus activity-regulated glioma growth, human intraoperative electrocorticography demonstrates increased cortical excitability in the glioma-infiltrated brain. Together, these findings indicate that synaptic and electrical integration into neural circuits promotes glioma progression.
Gesehen am 17.01.2020